Implementing Eco-Efficient Mercury Mitigation Strategies in Natural Gas Operations for Enhanced Sustainability - Onuoha Fidelis Wopara; Nnadikwe Johnson (Journal Majelis Paspama, 2026)
Mercury contamination in natural gas fields poses significant environmental and operational risks, particularly to brazed aluminum heat exchangers in LNG facilities and nitrogen rejection units. To address these concerns, this research evaluates eco-efficient mercury mitigation strategies for natural gas operations. Various mercury removal technologies are assessed, including metal sulfide adsorbents and activated carbons, with a focus on a gas project containing up to 70 µg/Sm3 of mercury. Technical and economic analysis reveals that sulfur-impregnated metallic oxide technology is the most suitable option for mercury removal. Key findings indicate that installing the mercury removal unit after the inlet separator and before CO2 removal minimizes mercury venting and pipe contamination. The bed's lifespan depends on feed gas pretreatment, and filtration is required regardless of location. Cost analysis shows metal oxide technology has the lowest CAPEX due to smaller vessel size and lowest overall cost over 25 years. Activated carbon beds have the cheapest single bed cost and OPEX, but similar lifespan to metal oxide beds. The proposed location works well with water-saturated gas below 95°C. Implementing these strategies enhances sustainability and protects equipment